A jurema sagrada em João Pessoa: um ritual em transição. - Ferreira, Sócrates Pereira (2011)
This dissertation will focus on practices from the rituals of the ancient catimbós da Jurema Sagrada in the city of Joao Pessoa and new features this religious phenomenon described by scholars prior to our century. For that utilizes the literature on the Jurema Sagrada and Umbanda in the level of Brazil and specifically in Paraiba and Joao Pessoa. From a methodological nature in the form of qualitative, descriptive, exploratory and the interviews were conducted in order to complement the observations made during the religious rituals of this matrix in the city of Joao Pessoa. We walked through the path of our bibliography of religious expression that originated in ancient indigenous descent passing through the city of Alhandra in Paraíba, to the inclusion of elements from Christian precepts to finally understand the current training and figures present in the Jurema Sagradas in the city of Joao Pessoa. The words of Mãe Penha de Iemajá and Pai Osias de Xangô, and those contribution about their experiences prior to the current year, both elected because of their importance in the history of the practices and traditions of the Jurema Sagrada and Umbanda. We describe and discuss in full ritual with the literature found, allowing the insertion of the words of our co-authors, by the insertion of the researcher in this context it was possible to collect data not previously explored in order hybrid religion in João Pessoa.